From Homeless to Student Housing: School Counselor Roles and Experiences in Preparing Students Experiencing Homelessness for College. Issue 1 (19th October 2021) - Havlik, Stacey; Duckhorn, Madeline; Rohrer, Shelby; Rowley, Patrick
This qualitative study focused on examining the roles and experiences of high school counselors supporting students experiencing homelessness in their college preparation. To be included in the study, participants needed to have experience working with high school students experiencing homelessness. Findings indicated that the participants supported students experiencing homelessness by (a) enhancing access and exposure to college, (b) providing hands-on and individualized college-going support, and (c) building partnerships with universities to support college going.